Dopaminergic regulation of nucleus accumbens cholinergic interneurons demarcates susceptibility to cocaine addiction - Lee, Joo Han (Biol Psychiatry, 2020)
BACKGROUND: Cholinergic interneurons (ChINs) in the nucleus accumbens (NAc) play critical roles in processing information related to reward. However, the contribution of ChINs to emergence of addiction-like behaviors and its underlying molecular mechanisms remain elusive. METHODS: We employed cocaine self-administration to identify two mouse subpopulations: susceptible and resilient to cocaine seeking. We compared the subpopulations for physiological responses with single-unit recording of NAc ChINs, and for gene expression levels with RNA sequencing of ChINs sorted using fluorescence-activated cell sorting. To provide evidence for a causal relationship, we manipulated the expression level of dopamine D2 receptor (DRD2) of ChIN in a cell-type specific manner. Using optogenetic activation combined with a double whole-cell recording, the effect of ChIN-specific DRD2 manipulation on each synaptic inputs were assessed in NAc medium spiny neurons (MSNs) in a pathway-specific manner. RESULTS: Susceptible mice showed higher levels of nosepoke responses under progressive ratio schedule, and impairment in extinction and punishment procedures. DRD2 was highly abundant in NAc ChIN of susceptible mice. Elevated abundance of DRD2 in NAc ChINs was sufficient and necessary to express high cocaine motivation, putatively through reduction of ChIN activity during cocaine exposure. DRD2 overexpression in ChINs mimicked cocaine-induced effects on the dendritic spine density and the ratios of excitatory inputs between two distinct MSN cell-types, while DRD2 depletion precluded cocaine-induced synaptic plasticity. CONCLUSIONS: These findings provide a molecular mechanism for dopaminergic control of NAc ChINs that can control the susceptibility to cocaine-seeking behavior.